(untitled) (Ta’limning zamonaviy transformatsiyasi, 2025)
Abstract: Developing strong reading and writing skills is essential for personal and academic growth. These skills enable individuals to comprehend, analyze, and communicate effectively. This article outlines practical strategies for improving reading and writing abilities, emphasizing the importance of consistency, critical thinking, and exposure to diverse materials. Key methods include setting goals, practicing regularly, and utilizing feedback to refine skills.